Effect of Stocking Density on the Growth of Siganus rivulatus Fingerling Reared in Tanks - إبراهيم, أمير; بدران, معينة; صالح, علاء (Latakia University Journal -Biological Sciences Series, 2021)
The study aimed to investigate the effect of stocking density on the growth of Siganus rivulatus, caught from the coastal area adjacent to the Higher Institute for Marine Research (35o35′30″N, 35o44′31″E). After acclimation, fingerlings were distributed into 6 strengthened polyethylene tanks 250 liters each under three densities 150 - 100 - 50 fish/tank with replicates. Fingerlings were fed twice a day to satiation and the hydrological features of the water were taken every day and the fish weights three times during the study period (70 days). The results showed that there was no significant difference between the 50 and 100 fish/tank densities (P>0.05), which gave an increase in weight by 6.57 and 6.5g/individual, respectively and had a feed conversion ratio of 2.47 and 2.49, respectively. On contrast, there was a significant difference between these two densities and that of 150 fish/tank (P<0.05), which had the lowest growth rate and lowest weight gain (5.59g/individual) and feed conversion rate (2.82).